Hormesis Shifts the No-Observed-Adverse-Effect Level (NOAEL) - Evgenios Agathokleous; Costas Saitanis; Athina Markouizou (SAGE Publishing, 2021)
Data from recent dose-response toxicological studies suggest that the no-observed-adverse-effect-level (NOAEL) may depend upon whether hormesis is present. A further examination of these data supports this hypothesis by showing that the NOAEL was greater for living units (organisms or cells) showing hormesis than for living units showing no hormesis. For example, some cancer tissue cells may exhibit hormetic responses to an anticancer drug while some other cancer tissue cells may not. These findings suggest that living units showing hormesis may also be less susceptible than living units not showing hormesis. However, these findings are preliminary and cannot be generalized or assumed to be a norm yet. New studies are needed to evaluate how NOAEL shifts depending on the occurrence of hormesis.